Dual light and temperature responsive cotton fabric functionalized with a surface-grafted spiropyran–NIPAAm-hydrogel. Issue 22 (23rd March 2016) - ter Schiphorst, J.; van den Broek, M.; de Koning, T.; Murphy, J. N.; Schenning, A. P. H. J.; Esteves, A. C. C.
Abstract : A dual-responsive cotton fabric functionalized with a spiropyran–NIPAAm hydrogel, capable of dimensional changes upon irradiation with visible light or upon a temperature stimulus is reported. Abstract : A dual-responsive cotton fabric functionalized with a spiropyran–NIPAAm hydrogel, capable of dimensional changes upon irradiation with visible light or upon a temperature stimulus is reported. These volume changes are due to absorption and release of water, from and into the air, by increasing temperature above the LCST in the dark, and/or by irradiation with sunlight or white light from artificial sources. The material was obtained via grafting photo- and temperature-responsive monomers directly from the cotton fibers, using a facile controlled polymerization method, ARGET ATRP.